The parental bonding in families of adolescents with anorexia: attachment representations between parents and offspring - Balottin L; Mannarini S; Rossi M; Rossi G; Balottin U (Neuropsychiatric Disease and Treatment, 2017)
Laura Balottin,1 Stefania Mannarini,1 Maura Rossi,2 Giorgio Rossi,3 Umberto Balottin2,4 1Interdepartmental Center for Family Research, Department of Philosophy, Sociology, Education, and Applied Psychology, Section of Applied Psychology, University of Padova, Padova, 2Child Neuropsychiatry Unit, C Mondino National Neurological Institute, Pavia, 3Child Neuropsychiatry Unit, Department of Experimental Medicine, University of Insubria, Varese, 4Child Neuropsychiatry Unit, Department of Brain and Behavioral Sciences, University of Pavia, Pavia, Italy Introduction: The attachment theory is widely used in order to explain anorexia nervosa origin, course and treatment response. Nevertheless, very little literature specifically investigated parental bonding in adolescents with anorexia, as well as the parents’ own bonding and intergenerational transmission within the family.Purpose: This study aims to identify any specific pattern of parental bonding in families of adolescents newly diagnosed with restricting-type anorexia, comparing them to the families of the control group.Patients and methods: A total of 168 participants, adolescents and parents (78 belonging to the anorexia group and 90 to the control one), rated the perceived parental styles on the parental bonding instrument. The latent class analysis allowed the exploration of a maternal bonding latent variable and a paternal one.Results: The main findings showed that a careless and overcontrolling parental style was recalled by the patients’ parents, and in particular by the fathers. As far as the adolescents’ responses were concerned, patients with anorexia did not seem to express differently their parental bonding perception from participants of the control group.Conclusion: Clinical implications driven from the results suggest that a therapeutic intervention working on how the parents’ own attachment representations influence current relationships may help to modify the actual family functioning and thus the outcome of patients with anorexia. Keywords: restricting-type anorexia nervosa, adolescence, parental bonding instrument, intergenerational transmission, latent class analysis, care and overprotection